Aspects and concerns separation in IS - Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2005)
The paper discusses howto proceed crosscutting concerns in enterprise information sistems, which include computer-aided as well as manual information processing procedures. It proposes to consider such systems as component systems including diferent level components: business components, information processing components and software components. All components should be treated in an uniform manner and modelled using appropriate use case models. Using the proposed approach, croscutting concerns are tangled with functional concerns at the use case level. After this, software components are implemented using conventional techniques of aspect-oriented programming and other components in the form of guides and manuals how to performmanual and computer-aided procedures.